2013
DOI: 10.1111/joa.12030
|View full text |Cite
|
Sign up to set email alerts
|

Expression of orexin A and its receptor 1 in the human prostate

Abstract: The peptides orexin A (OXA) and orexin B, deriving from the cleavage of the precursor molecule prepro-orexin, bind two G-coupled transmembrane receptors, named as receptor 1 (OX1R) and receptor 2 for orexin, showing different affinity-binding properties. First discovered in the rat hypothalamus, orexins and their receptors have been also found in many peripheral tissues where they exert neuroendocrine, autocrine and paracrine functions. Because inconclusive data on their localization in the mammalian prostate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…Recently, three reports have published data on the presence of OXA-LI in normal human prostate, BPH and in prostate cancer (PC) [17,18,30]. In two of them IHC reaction products for ppOX and OXA were observed in the epithelium of human normal and hyperplastic prostatic glands and the presence of ppOX protein was confirmed by Western blotting.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Recently, three reports have published data on the presence of OXA-LI in normal human prostate, BPH and in prostate cancer (PC) [17,18,30]. In two of them IHC reaction products for ppOX and OXA were observed in the epithelium of human normal and hyperplastic prostatic glands and the presence of ppOX protein was confirmed by Western blotting.…”
Section: Discussionmentioning
confidence: 96%
“…The French group, on the other hand, observed OXA-LI in 'fiber-like' structures of the stroma and no reaction was observed in cancerous foci of PC [30]. Moreover, Valiante et al [17,18] demonstrated also expression of ppOX by means of RT-PCR. In light of these discrepancies we performed studies on the expression of ppOX in 6 human prostatic cell lines -LNCaP; Du145; PC3; PrEC; PrSmC and PrSc.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations